2017
DOI: 10.3991/ijet.v12i09.7482
|View full text |Cite
|
Sign up to set email alerts
|

3DBody Software Experimental Platform for Course of Sports Anatomy

Abstract: Abstract-Sports anatomy is one of the important basic subjects of sports colleges and universities. As multimedia network technology increasingly matures and is popularized, it becomes an irresistible trend to transform the traditional teaching mode of sports anatomy into multimedia network teaching mode. Thus, a new-type experimental platform based on action-orientated approach and provided with MVC framework and 3DBody experimental software is put forward in this paper, and it is analyzed and interpreted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Despite the benefits of 3D tools for student learning and knowledge acquisition, some studies have found no significant differences between modern 3D learning resources, traditional 2D approaches, and dissections in terms of student human anatomy knowledge acquisition [4,5,[7][8][9][10][11][12][13][14]. However, studies conducted in different universities in Saudi Arabia suggested 3D-VR as an excellent teaching methodology to improve student human anatomy knowledge retention [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of 3D tools for student learning and knowledge acquisition, some studies have found no significant differences between modern 3D learning resources, traditional 2D approaches, and dissections in terms of student human anatomy knowledge acquisition [4,5,[7][8][9][10][11][12][13][14]. However, studies conducted in different universities in Saudi Arabia suggested 3D-VR as an excellent teaching methodology to improve student human anatomy knowledge retention [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It covers nine systems of the human body, including systematic, topographic, and sectional anatomies. Ren et al [8] indicated that applying the 3DBody software in the classroom could significantly enhance students' enthusiasm for learning human anatomy. Researchers [9][10] adopted the 3DBody software to study anatomy and indicated that such software could solve the problems pertaining to the traditional wall map of anatomy, such as poor third dimension, model distortion, and specimen source deficiency.…”
Section: State Of the Artmentioning
confidence: 99%
“…Therefore, how to avoid or reduce the occurrence of sports injuries of Competitive Wushu routine athletes is an urgent problem to be solved in the development of Wushu routine sports. This study attempts to use multi-disciplinary theories and methods, including sports training [2], biomechanics [3], sports anatomy [4], etc., to investigate and study the characteristics of sports injuries of Wushu routine athletes from multiple perspectives and levels, and to provide corresponding preventive countermeasures. It can provide reference for the teaching and training of Wushu routine and the prevention of sports injury in the competition.…”
Section: Introductionmentioning
confidence: 99%